The impact of macroeconomics factor on money supply / Ain Syafiqah Khairullah - Khairullah, Ain Syafiqah (Faculty of Business and Management, 2020)
Many scientists in developed countries have examined the significance of money supply to macroeconomics. However, few studies in developing nations have investigated this proposal. In this research, panel data from year 2002 until 2018 were collected annually to analyse and investigate the relationship between the money supply (M2) and the macroeconomic variables (Gross Domestic Product, Inflation Rate, Interest Rate, Foreign Exchange Rate and Population Growth) among nine (9) Asian countries which is Malaysia, India, Philippine, Singapore, Thailand, Brunei, China, Japan and Sri Lanka. This study’s aim is to analyse the effect of these factors on all nine (9) Asian countries’ money supply. After conducting a Best Regression Random Effect Model, it can be concluded that Gross Domestic Product and Inflation Rate have a positive significant relationship with money supply while Interest Rate, Population Growth and Foreign Exchange Rate have a positive insignificant relationship with money supply